1998
DOI: 10.1128/aem.64.8.2763-2769.1998
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Lactococcal nisA Promoter To Regulate Gene Expression in Gram-Positive Bacteria: Comparison of Induction Level and Promoter Strength

Abstract: We characterized the regulated activity of the lactococcalnisA promoter in strains of the gram-positive species Streptococcus pyogenes, Streptococcus agalactiae, Streptococcus pneumoniae,Enterococcus faecalis, and Bacillus subtilis. nisA promoter activity was dependent on the proteins NisR and NisK, which constitute a two-component signal transduction system that responds to the extracellular inducer nisin. The nisin sensitivity and inducer concentration required for maximal induction varied among the strains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(71 citation statements)
references
References 47 publications
4
67
0
Order By: Relevance
“…The later does not require any modifications to the host bacterium and thus has a broader host range. The lactococcal NICE system has been well characterized and shown to function properly in several LAB species (Kleerebezem et al 1997;Eichenbaum et al 1998). Tightly regulated gene expression has been reported for the NICE system (de Ruyter et al 1996a); however, PnisA has been shown to be 'leaky' in some LAB allowing for reduced gene expression in the absence of nisin as an inducer (Brondsted et al 2001;Fu et al 2005;Hazebrouck et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The later does not require any modifications to the host bacterium and thus has a broader host range. The lactococcal NICE system has been well characterized and shown to function properly in several LAB species (Kleerebezem et al 1997;Eichenbaum et al 1998). Tightly regulated gene expression has been reported for the NICE system (de Ruyter et al 1996a); however, PnisA has been shown to be 'leaky' in some LAB allowing for reduced gene expression in the absence of nisin as an inducer (Brondsted et al 2001;Fu et al 2005;Hazebrouck et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The system is dependent on the products of the nisRK genes which constitute a two-component regulatory system, which senses exogenous nisin and induces gene expression from the nisA promoter (PnisA) (Kuipers et al 1995). This system was shown to function properly in numerous LAB species (de Ruyter et al 1996a;Kleerebezem et al 1997;Eichenbaum et al 1998), and has been used to increase expression of the chimeric lactococcin A-pediocin PA-1 peptide in L. lactis (Horn et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the highest b-glucuronidase specific activity levels were detected after induction for 3 h using of 10 ng ml À1 of nisin. Similar expression systems developed for L. plantarum [4] and other Gram-positive hosts [13] required higher nisin concentrations (20-25 ng ml À1 ) Fig. 1.…”
Section: Functional Analysis Of the Nice System In L Casei Atcc 393mentioning
confidence: 95%
“…This system (NICE) was subsequently introduced into other LAB [4,13] ATCC393, the strain of the genus for which more efficient genetic manipulation tools have been developed. An essential prerequisite to get a functional NICE expression system is the availability of a strain producing NisR and NisK.…”
Section: Introductionmentioning
confidence: 99%
“…The genes and promoters involved in nisin production have been used to develop a nisin-controlled expression (NICE) system for efficient, regulated overproduction of heterologous proteins in lactococci (de Ruyter et al 1996), lactobacilli (Pavan et al 2000), and other Gram-positive bacteria (Eichenbaum et al 1998). Similar systems may be developed on the basis of genes and promoters involved in the production of class II bacteriocins.…”
Section: Introductionmentioning
confidence: 99%